1975
DOI: 10.1121/1.2001926
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for turtle auditory localization

Abstract: Evidence is presented that the semiaquatic turtle Pseudemys scripta and the terrestial turtle Terrapene carolina major can detect the direction of a tone within their sensitive area of hearing. The stimulus was a 5% modulated 500-Hz tone generated in a Y maze with speakers at a 45° angle. The SPL at the discrimination area of the maze was 82 dB. Only one turtle of each species met the criteria of either ten consectuve correct responses or an overall 75% correct response level. However, all other animals respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Auditory evoked potential (AEP) testing, in which electrodes are used to detect voltages generated by the brain in response to acoustic stimuli, supports findings that terrestrial turtles have low-frequency hearing with best sensitivity below 1kHz (Adrian et al, 1938;Wever and Bray, 1931;Wever and Vernon, 1956a;Wever and Vernon, 1956b;Wever and Vernon, 1956c). Terrestrial turtles are also able to behaviorally respond to sound stimuli (Andrews, 1915;Patterson, 1966) and even learn complex behaviors like maze navigation in response to directional sound cues (Lenhardt, 1981).…”
Section: Introductionmentioning
confidence: 78%
“…Auditory evoked potential (AEP) testing, in which electrodes are used to detect voltages generated by the brain in response to acoustic stimuli, supports findings that terrestrial turtles have low-frequency hearing with best sensitivity below 1kHz (Adrian et al, 1938;Wever and Bray, 1931;Wever and Vernon, 1956a;Wever and Vernon, 1956b;Wever and Vernon, 1956c). Terrestrial turtles are also able to behaviorally respond to sound stimuli (Andrews, 1915;Patterson, 1966) and even learn complex behaviors like maze navigation in response to directional sound cues (Lenhardt, 1981).…”
Section: Introductionmentioning
confidence: 78%
“…Published evidence of localization in other turtle species is presented by Lenhardt (1981). Looking at the semiaquatic turtle, Chrysemys scripta, and the terrestrial turtle, Terrapene carolina major, Lenhardt (1981) observed behavioral patterns indicative of sound localization.…”
Section: Plos Onementioning
confidence: 98%
“…Sound may be perceived by hatchlings as a function of both aerial acoustic cues and the accompanying vibrations these sounds produce. Lenhardt (1981) hypothesized that turtles use bone conduction in sound perception by coupling their ear to the substrate [42]. We eliminated vibrations from our study by suspending the speaker off of the ground and arena table.…”
Section: Plos Onementioning
confidence: 99%
“…Stellar or lunar cues appear to be used by alligators, Alligator mississippiensis, 38 vibrational cues have been shown to be used for orientation by the sand-swimming lizard, Scincus scincus, 39 and acoustic cues were shown to be used by the pond turtle, Chrysemys scripta. 5 Geomagnetic cues have been shown to be used by several species of sea turtles 40,41 and alligators. 42 The work in sea turtles is notable because it has been shown that hatchlings first find the ocean by reflected light from the ocean's surface and then swim seaward by using the wave orientation.…”
Section: Orientation Cuesmentioning
confidence: 99%
“…Fewer studies on spatial learning have been conducted in reptiles (the evolutionary ancestors of both birds and mammals). Most spatial learning studies in reptiles have been conducted primarily in turtles and tortoises, [4][5][6][7] and very few spatial learning studies have used lizards and snakes. 4,8 Snakes may be more dependent on their environment than mammals and birds and, possibly, other ectotherms.…”
mentioning
confidence: 99%